Clinical profile and predictors of in-hospital mortality among older patients hospitalised for COVID-19 - Becerra-Muñoz, Víctor Manuel; Núñez-Gil, Iván J; Eid, Charbel Maroun; García Aguado, Marcos; Romero, Rodolfo; Huang, Jia; Mulet, Alba; Ugo, Fabrizio; Rametta, Francesco; Liebetrau, Christoph; Aparisi, Alvaro; Fernández-Rozas, Inmaculada; et al. (Age & ageing, 2021)
the coronavirus disease 2019 (COVID-19) is characterized by poor outcomes and mortality, particularly in older patients.post hoc analysis of the international, multicentre, ‘real-world’ HOPE COVID-19 registry. All patients aged ≥65 years hospitalised for COVID-19 were selected. Epidemiological, clinical, analytical and outcome data were obtained. A comparative study between two age subgroups, 65-74 and ≥75 years, was performed. The primary endpoint was all cause in-hospital mortality.about, 1,520 patients aged ≥65 years (60.3% male, median age of 76 [IQR 71-83] years) were included. Comorbidities such as hypertension (69.2%), dyslipidaemia (48.6%), cardiovascular diseases (any chronic heart disease in 38.4% and cerebrovascular disease in 12.5%), and chronic lung disease (25.3%) were prevalent, and 49.6% were on ACEI/ARBs. Patients aged 75 years and older suffered more in-hospital complications (respiratory failure, heart failure, renal failure, sepsis) and a significantly higher mortality (18.4 vs. 48.2%, P < 0.001), but fewer admissions to intensive care units (11.2 vs. 4.8%). In the overall cohort, multivariable analysis demonstrated age ≥75 (OR 3.54), chronic kidney disease (OR 3.36), dementia (OR 8.06), peripheral oxygen saturation at admission <92% (OR 5.85), severe lymphopenia (<500/mm3) (OR 3.36) and qSOFA (Quick Sequential Organ Failure Assessment Score) >1 (OR 8.31) to be independent predictors of mortality.patients aged ≥65 years hospitalised for COVID-19 had high rates of in-hospital complications and mortality, especially among patients 75 years or older. Age ≥75 years, dementia, peripheral oxygen saturation <92%, severe lymphopenia and qSOFA scale >1 were independent predictors of mortality in this population.